2018
DOI: 10.37637/ab.v1i2.310
|View full text |Cite
|
Sign up to set email alerts
|

PENGARUH DOSIS PETROGANIK TERHADAP PERTUMBUHAN DAN HASIL TIGA VARIETAS KACANG HIJAU (Phaseolus radiatus Linn.) DI LAHAN KERING

Abstract: Penelitian ini dilaksanakan di Banjar Dinas Muntigunung, Desa Tianyar Barat, Kecamatan Kubu, Kabupaten Karangasem dari bulan Desember 2014 sampai dengan Pebruari 2015.  Percobaan menggunakan Rancangan Petak Terpisah (split plot desgn) dengan dasar rancangan acak kelompok (RAK), terdiri dari  dua faktor,  yaitu varietas dan Dosis Pupuk Petroganik. Varietas terdiri dari 3 jenis, yaitu Vima-1, Murai dan Lokal Wono Sari. Dosis pupuk petroganik terdiri dari 3 taraf, yaitu 4 ton.ha-1, 8 ton.ha-1dan 12 ton.ha-1.  Var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
1
0
2
Order By: Relevance
“…In accordance to organic fertilization, showed the increased of fresh and dry weight in real time 56.23% and 42.02% each that the application of organic fertilizer with the dose of 20 tons/ha, in contrast with the plot without organic fertilizer. This in accordance with Suarsana, et al (2018), where the increase of petroganic dose to 8 tons/ha gave a higher dry and wet matter (10% and 8.8%) compared with 4 tons/ha dose of petroganic.…”
Section: Fresh and Dry Matter Weightsupporting
confidence: 90%
See 1 more Smart Citation
“…In accordance to organic fertilization, showed the increased of fresh and dry weight in real time 56.23% and 42.02% each that the application of organic fertilizer with the dose of 20 tons/ha, in contrast with the plot without organic fertilizer. This in accordance with Suarsana, et al (2018), where the increase of petroganic dose to 8 tons/ha gave a higher dry and wet matter (10% and 8.8%) compared with 4 tons/ha dose of petroganic.…”
Section: Fresh and Dry Matter Weightsupporting
confidence: 90%
“…This is the same with the research of Malau, et al (2015) which found that the increase of organic fertilizer as many as 750 kg/ha (0.75 tons/ha) could give a real effect for the increase of 100 beans weight in comparison to the control. Suarsana, et al (2018) and Mayani, et al (2021) stated that the increase of organic fertilization each for 8 ton/ha and 7.5 tons/ha could increase 100 seeds weight in comparison to the control. Organic fertilizer according to Leiwakabessy, et al (2003) is used to repair the soil structure; increase the availability of N, P, and S substances; increase the cation exchange capacity (CEC); and activate the microorganism.…”
Section: Hundred Seed Weightmentioning
confidence: 99%
“…Rendahnya produktivitas pakcoy ini dipengaruhi oleh berbagai faktor. Faktor penting yang diyakini dapat mempengaruhi pertumbuhan dan produksi tanaman adalah ketersediaan unsur hara dalam tanah (Suarsana et al, 2018). Unsur hara makro yang paling banyak dibutuhkan oleh tanaman pakcoy adalah unsur nitrogen (N), fosfor (P) dan kalium (K) yang berfungsi meningkatkan dan mempercepat lagu pertumbuhan vegetatif dan pembentukan protein tanaman (Putri dan Santoso, 2014).…”
Section: Pendahuluanunclassified
“…Optimalisasi penyerapan unsur hara dari lingkungan tumbuh dipengaruhi oleh sifat genetik tanaman atau ekspresi gen pada tanaman dan penyesuaian tanaman terhadap kondisi lingkungan sehingga jumlah unsur hara yang diserap bervariasi antargenotipe. Perbedaan kemampuan tersebut kemudian ditunjukkan pada perbedaan karakter vegetatif dan generatif tanaman seperti tinggi tanaman, bobot biomas, dan bobot biji (Suarsana et al 2018;Achakzai et al 2012).…”
Section: Pendahuluanunclassified